2012
DOI: 10.1093/aje/kws193
|View full text |Cite
|
Sign up to set email alerts
|

Sleep Disturbance and Incidence of Thyroid Cancer in Postmenopausal Women The Women's Health Initiative

Abstract: Sleep disturbance has been found to be associated with numerous adverse health outcomes, including cancers. However, no epidemiologic study has examined the relation between sleep disturbance and thyroid cancer risk. A total of 142,933 postmenopausal women who were 50-79 years of age and enrolled in the Women's Health Initiative between September 1, 1993, and December 31, 1998, were followed up for a mean of 11 years. Cox proportional-hazard regression models were used to estimate hazard ratios and 95% confide… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
51
1
2

Year Published

2013
2013
2021
2021

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 72 publications
(56 citation statements)
references
References 47 publications
2
51
1
2
Order By: Relevance
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…Finally, 12 articles fulfilling the inclusion criteria were included in the meta-analysis. Among these 12 articles, five studies reported breast cancer (Verkasalo et al, 2005;Pinheiro et al, 2006;Kakizaki et al, 2008b;Vogtmann et al, 2013;Wu et al, 2013), two studies on colorectal cancer (Jiao et al, 2013;Zhang et al, 2013), one each study on prostate cancer (Kakizaki et al, 2008a), endometrial cancer (Sturgeon et al, 2012), epithelial ovarian cancer (Weiderpass et al, 2012), thyroid cancer (Luo et al, 2013), and all type cancers (von Ruesten et al, 2012).…”
Section: Search Resultsmentioning
confidence: 99%
“…Nine studies focused on the cancer of women, one only on men (Kakizaki et al, 2008a), one on men and women combined (von Ruesten et al, 2012), and one reporting men and women separately according to different cohorts (Zhang et al, 2013). Most of studies reported the sleep duration of 24 hours period, while four studies investigated typical night sleep duration (Sturgeon et al, 2012;Jiao et al, 2013;Luo et al, 2013;Vogtmann et al, 2013). In most of the studies, cancer was assessed by self-reported and confirmed by adjudicators via medical record review, four studies identified cancers through cancer registry data (Verkasalo et When results were reported for men and women separately, it was entered into meta-analysis as separate studies.…”
Section: Study Characteristicsmentioning
confidence: 99%
See 1 more Smart Citation
“…Similar results can be found for people with profound sleep disturbances not necessarily caused by occupation (Hublin et al, 2007;Kondratov et al, 2007;Adamantidis and de Lecea, 2008). Intriguingly, this increased risk extends to several cancers, but is most commonly seen in hormonally regulated cancers such as breast, prostate, ovarian, and thyroid cancer (Davis et al, 2001;Hansen, 2001;Anisimov, 2003;Schernhammer et al, 2003;Megdal et al, 2005;Anisimov, 2006;Kubo et al, 2006;Schernhammer et al, 2006;Hansen and Stevens, 2011;Poole et al, 2011;Monsees et al, 2012;Luo et al, 2013). In fact, the International Agency for Research on Cancer Working Group concluded that shift-work with circadian disruption is probably carcinogenic to humans (Straif et al, 2007).…”
Section: Circadian Disruption In Humans and The Melatonin Hypothesismentioning
confidence: 54%
“…9 ). A new study based on the large Women's Health Initiative cohort of over 100,000 postmenopausal women found women with worse insomnia scores (based on symptoms of insomnia) were about 44 % more likely to develop thyroid cancer [ 13 ].…”
Section: Insomniasmentioning
confidence: 99%